Effect of clearing native forest (Caatinga) strips on some hydrologic components of micro-watersheds - Sharma, Prem N.; Silva, Aderaldo de S. (Pesquisa Agropecuaria Brasileira, 2014)
The influences of clearing native vegetation (Caatinga) in contour strips at 25 cm vertical interval on evaporation losses in cleared strips, annual runoff efficiency and annual soil loss on gently sloped micro-watersheds in the arid zones of Northeast Brazil are reported. The alternate native vegetation (Caatinga) strips function very effectively as windbreaks thus reducing evaporation losses substantially in the leeward cleared strips. The runoff measured at the micro-watershed with cleared strips was many-fold lower than the runoff obtained at a completely denuded watershed even when it was protected by narrow based channel terraces. However, the annual runoff efficiency can be significantly increased in a strip cleared watershed if narrow based channel terraces are provided on the lower side of cleared strips. The annual soil losses in strip cleared watersheds as well as completely denuded watershed of gentle slopes were negligible. Thus clearing land in alternate contour strips on a micro-watershed shall substantially improve crop water use efficiency without creating any significant erosion problems. Additionally this treatment will increase runoff for water harvesting for irrigation purposes.
Keywords: forest watershed management; windbreaks; irrigation of arid lands